217k views
0 votes
What is the answer to -3^-3

2 Answers

7 votes

Answer:


\Huge \boxed{-(1)/(27)=-0.03703}

Explanation:

To solve this problem, first you have to use the exponent rule of
\displaystyle a^-^c=(1)/(a^c). Remember to solve this problem, order of operations stands for parenthesis, exponents, multiply, divide, add, & subtract from left to right.

First, multiply numbers from left to right.


\displaystyle 3^3=3*3*3=27

Therefore, the correct answer is -1/27.

2 votes
-3^-3=-1/3^3=-1/27
Indeed.
User Mayank Majithia
by
5.9k points